Birinci basamak sağlık hizmetlerinde çalışan hemşirelerin özürlü bireylere yönelik tutumunun sağlık eğitimi faaliyetlerine etkisi - Ayyıldız, Nihal (My University, 2013)
Araştırmanın amacı; birinci basamak sağlık hizmetlerinde çalışan hemşirelerin özürlü bireylere ilişkin tutumunun özürlü bireylere yönelik sağlık eğitimi faaliyetlerine etkisini belirlemektir. Araştırmanın evrenini, İstanbul ilindeki 8 sağlık grup başkanlığı ve 120 sağlık ocağında çalışan 278 hemşire; örneklemini ise ulaşılan ve araştırmaya katılmaya gönüllü 181 hemşire oluşturmuştur. Veriler, 18 sorudan oluşan anket formu ve 43 ifadeden oluşan Özürlülere Yönelik Tutum Ölçeği ile elde edilmiştir. Hemşirelerin yaş ortalaması 32 yıl, mesleki deneyimi ortalaması 11 yıl, birinci basamak sağlık hizmetlerinde çalışma deneyimi ortalaması 6 yıldır. Hemşirelerin, %87.3‟ü özürlü bireylerle nadiren karşılaştığını, yarıdan fazlası özürlü bireylere yönelik herhangi bir eğitim almadığını ifade etmiştir. Hemşirelerin %95.6‟sı kurumlarında özürlü bireylere yönelik eğitim materyallerinin bulunmadığını, eğitim verirken en çok zihinsel özürlü bireylerde güçlük çektiğini (%58.7), zihinsel özürlü bireylere sağlık eğitimi vermek istemediğini (%45.9) belirtmiştir. Hemşirelerin özürlülere yönelik tutumu olumlu yöndedir (Ölçek toplam puanı:169.07). Hemşirelerin yaşı ve mesleki deneyimi ile özürlülere yönelik tutumu arasında negatif yönde zayıf derecede ilişki vardır. Özür tür ve derecesine uygun eğitim materyali güçlüğü yaşayan hemşirelerin özürlü bireylere yönelik tutumu daha olumludur. lık eğitimi, özürlü birey, tutum, hemşire

The Effect of the Attitudes of the Nurses Employed at Primary Health Services towards the People with Disabilities on Health Education Activities The purpose of this study is to determine the effect of the attitudes of the nurses employed at primary health services towards the people with disabilities on health education activities for these people. The population of the study consisted of 278 nurses from 8 health group directories and 120 community health centers in Istanbul and 181 voluntary nurses who were contacted and accepted to participate formed the sample of the study. The data was obtained by using an 18-item-questionnaire and an Attitude Scale towards the People with Disabilities, which contained 43 statements. The average age of the nurses was 32; the average year of the experience in the profession was 11; and the experience average year of the nurses at primary health services was 6. It was found that 87.3% of the nurses rarely treated the people with disabilities and more than half of them expressed that they did not have any education for the people with disabilities. 95.6% of the nurses stated that there were no educational materials for the people with disabilities in their institutions while 58.7% of them expressed that they had the most difficulty while education the mentally disabled. 45.9% of the nurses indicated that they did not want to train the mentally disabled at all. However, the attitudes of the nurses towards the people with disabilities were positive (Scale total point is 169.07). There is a slight negative relationship between the age and professional experience of the nurses and their attitudes towards the people with disabilities. The attitude of the nurses who had difficulty in finding education materials adequate for the type of the handicap and its level was more positive towards the people with disabilities. Key Words: Health education, people with disabilities, attitude,
Keywords: Eğitim; Fiziksel Engelliler; Fiziksel Özürlüller; Hemşireler; Sağlık; Zihinsel Engelliler; Zihinsel Özürlüler